Influence of service quality, university image, the mediating effect of organizational commitment relationship marketing and adoption of technology innovation loyalty in Nigeria - Usman, Umar (2017)
his study delves into the mediating effect of student satisfaction on the relationship that has been established between service quality, university image, commitment, trust and student loyalty, and the moderating role of technology innovation on the link between student satisfaction and loyalty in higher education institutions (HEIs) in Nigeria. Responding to the decline in HEIs funding, this study evaluated the factors that influence student loyalty in these institutions. Questionnaires were distributed to 535 students from various Nigerian federal universities. The Statistical Package for Social Sciences (SPSS 22) and the Partial Least Squares (PLS) served to check the hypotheses. The path analysis results lend support to the relationshipbetween service quality, university image, commitment, trust, student satisfaction and student loyalty. In a similar manner, the mediating effect of student satisfaction was found on the relationship between university image, commitment, trust and student loyalty. Nonetheless, student satisfaction did not mediate the relationship between service quality and student loyalty. Additionally, technology innovation moderated the relationship between student satisfaction and loyalty. Findings of this study, therefore, imply that service quality, university image, commitment, trust, technology innovation influence the level of student satisfaction and loyalty positively. The main drawback of this study is that the basis of the findings only rests on post-graduate and undergraduate students from the Nigerian federal universities in Nigeria and excludes the private higher education institutions. The findings can help policy-makers within the HEIs to lay out strategic decisions that will improve students‘ satisfaction and loyalty. Next, the theoretical implications and suggestions for future research are discussed and the impending conclusion is made.